Evaluasi Model CIPP Pembelajaran Bahasa Indonesia di Sekolah Menengah Pertama Negeri 1 Seririt - Santini, Ni Made Ayu Putri; Sudiana, I Nyoman; Dewantara, I Putu Mas (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – The purpose of this study was to find out the application of the implementation of Indonesian language learning based on the Merdeka Curriculum at SMPN 1 Seririt with the evaluation of the CIPP (Context, Input, Process, Product) model.Method – This research is qualitative research that uses the CIPP model by evaluating each component of the context, input, process and product to achieve an effective learning process. Sources of research data were Indonesian language teachers, curriculum representatives, and school principals at SMPN 1 Seririt. Data collection using observation instruments, documentation, and interviews. The data is then analyzed by descriptive qualitative.Findings – The study reveals that the context, input, process, and product components in Indonesian language learning at SMPN 1 Seririt are overall good. Context evaluation, covering school profile, teacher preparation, learning activities, observations, and teacher feedback, is rated positively. Input evaluation shows the teaching staff’s educational background (Bachelor's and master’s in education) and material mastery as good, though teachers sometimes overly rely on textbooks. Information technology is used but infrequently, and facilities adequately meet both student and teacher needs. The process evaluation indicates that planning and implementing Indonesian language learning in the Merdeka Curriculum is fairly effective. Product evaluation through formative and summative assessments highlights listening as the most mastered skill, with writing as the least. Research Implications – The findings suggest that the Indonesian language curriculum should be more student-centered and incorporate interactive teaching methods. Enhancements in comprehensive assessment, teacher training, and increased parental and community engagement are essential for improving education quality.